The Effect of Environmental, Social, and Governance Disclosure on Stock Returns with Firm Value as an Intervening Variable: Study on Companies Listed in the SRI-KEHATI Index - Andika Budhiananto, Hanifa; ‎ , Fatimah (KnE Social Sciences, 2024)
The concept of environmental, social, and governance (ESG) has significantly become a trend in the world economy and capital markets. More and more companies, globally, are encouraged to adopt ESG as an effort toward business sustainability. However, the situation or implementation of ESG in Indonesia is challenging, and it is currently in the development stage for regulators, companies, and potential investors. By using sustainable reporting standards, which the Otoritas Jasa Keuangan launched through POJK No. 51 of 2017, this research will contribute to future research with similar topics on sustainable finance. It can also be considered for companies in Indonesia to apply ESG principles as a non-financial indicator regarding transparency and accountability to stakeholders in making investment decisions. This study aims to analyze the effect of ESG disclosure on stock returns with firm value as an intervening variable, especially for companies listed in the SRI-KEHATI stock index. The analysis used the panel data regression and path analysis method with EViews 9 software. The sample selection used a purposive sampling technique totaling 41 samples from 5 years of observation. The results found that ESG disclosure has no effect on stock returns but affects negatively on firm value. Firm value proxied by Tobin’s Q can negatively mediate the effects of ESG disclosure on stock returns. Keywords: ESG disclosure, SRI-KEHATI index, stock return, firm value, tobin’s Q